Cztery wielkie nurty w metodologii XX wieku - Sady, Wojciech (Filozofia Nauki, 1996)
All significant methodologies of the XX century accept conventionalistic philosophy of science. The main question for such methodologies is: are there universal criteria, allowing to choose these conventions, which are the best from the cognitive point of view? There are four classical answers to this problem: anarchism, sociologism, elitism and demarcationism. In the article the main dillemas of demarcationist program are considered.